2018
DOI: 10.1002/admi.201800248
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Interface Engineering for Organic Metal Halide Perovskite–Based Photovoltaic Cells

Abstract: Organic–inorganic metal halide perovskite (OMHP) has become one of the most important optoelectronic materials due to its electronic transport properties and excellent machinability. The efficiency of OMHP solar cells has risen rapidly from 3.81% to more than 20% in the past seven years, which has almost approached the theoretical value. Despite the continuous and in‐depth researches by scientists, it has been difficult to prepare new materials for OMHP devices with high performances. According to literature r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 214 publications
1
15
0
Order By: Relevance
“…To understand the carrier dynamics in HOPs of type ABX 3 , detailed research into the atomic and electronic structures of these materials, which are always more complex than those of conventional optoelectronic devices, is required. [30] These perovskites form crystalline structures that contain organic Asite cations within the angular octahedral inorganic skeleton BX 3 (Figure 1a). Substitution at the sites of X (X = Cl − , Br − , I − ), B (B = Pb 2+ ), or = + + A (A CH NH , HC(NH ) 3 3 2 2 ) leads to a variety of different chemical and physical properties.…”
Section: Crystal Structures and Lattice Dynamicsmentioning
confidence: 99%
See 4 more Smart Citations
“…To understand the carrier dynamics in HOPs of type ABX 3 , detailed research into the atomic and electronic structures of these materials, which are always more complex than those of conventional optoelectronic devices, is required. [30] These perovskites form crystalline structures that contain organic Asite cations within the angular octahedral inorganic skeleton BX 3 (Figure 1a). Substitution at the sites of X (X = Cl − , Br − , I − ), B (B = Pb 2+ ), or = + + A (A CH NH , HC(NH ) 3 3 2 2 ) leads to a variety of different chemical and physical properties.…”
Section: Crystal Structures and Lattice Dynamicsmentioning
confidence: 99%
“…In 2016, a new prop erty of Fe based HOPs was found. [178] When [CH 3 NH 2 CH 3 ] [Fe(HCOO) 3 ] and [NH 3 OH][Fe(HCOO) 3 ] were considered, it was found that their spin states changed remarkably with changes in the environment. As Figure 12d shows, their mag netic moments shift as the pressure changes.…”
Section: Pressure Sensorsmentioning
confidence: 99%
See 3 more Smart Citations